Development of Peer Assessment Social Behaviour Instrument on Learning Mathematics In Junior High School - Windrianti, Maria Gerrin; Kartono, Kartono; Ridlo, Saiful (Journal of Research and Educational Research Evaluation, 2018)
Social behaviour is one of the aspects assessed in the process of applying the Curriculum 2013. Social behaviour includes aspects of honest, disciplined, courtesy, confident, caring, and responsibility. This study aims to develop an instrument of social behaviour through peer assessment on mathematics learning in junior high school that are valid and reliable. The research method used is development research with modified Sugiyono model. Content validity through expert judgment is tested using V index and its reliability with ICC. Small-scale trials were tested with pearson correlation and alpha cronbach for reliability. Large-scale trials were tested using Confirmatory Factor Analysis 2nd Order, and its reliability with the Construct Reliability formula. The results of the validation of experts obtained 35 items valid and reliable. A small-scale trial with 52 respondents, 27 valid grains with coefficient> 0.3 and reliability were 0.805. In large scale trials, 25 items have construct validity with estimated loading factor (ÃŽÂ»)> 0.30. The test result using SEM meets Godness of Fit if RMSEA show value 0,017; GFI shows a value of 0.87, AGFI shows a value of 0.84 and RMSR shows a value of 0.041. Instrument expressed practical with the questionnaire score> 21. The results showed that the instrument of social attitudes through peer assessment developed valid and reliable.